Faktor-faktor yang mempengaruhi kebijakan dividen - DIKI HARIANTO; DEWI AGUSTINA (Jurnal Bisnis dan Akuntansi, 2016)
The objective of this research is to get empirical evidence the influence of earnings per share, return on equity, operating cash flow, size, institutional ownership, debt policy, and managerial ownership to dividend policy. Data is collected from manufacturing companies in Indonesian Stock Exchange (IDX) for four years period 2009–2012. Sample selected by using purposive sampling method. Only 34 companies meet the criteria and taken as sample. The statistical method used in this research is multiple regression. The result of this research showed that earnings per share and institutional ownership have influence to dividend policy but return on equity, operating cash flow, size, debt policy, and managerial ownership have no influence to dividend policy. The objective of this research is to get empirical evidence the influence of earnings per share, return on equity, operating cash flow, size, institutional ownership, debt policy, and managerial ownership to dividend policy. Data is collected from manufacturing companies in Indonesian Stock Exchange (IDX) for four years period 2009–2012. Sample selected by using purposive sampling method. Only 34 companies meet the criteria and taken as sample. The statistical method used in this research is multiple regression. The result of this research showed that earnings per share and institutional ownership have influence to dividend policy but return on equity, operating cash flow, size, debt policy, and managerial ownership have no influence to dividend policy.